Stakeholder Perceptions About The Establishment Of Medical Simulation-Based Learning At A University In A Low Resource Setting: A Qualitative Study In Uganda - Najjuma, Josephine Nambi; Bajunirwe, Francis; Twine, Margaret; Namata, Tamara; Kyakwera, Catherine Kalimba; Cherop, Moses; Santorino, Data (BMC Medical Education, 2020)
Simulation based learning (SBL) is a technique where teachers recreate “real life” clinical experiences for health care teams for purposes of gaining clinical skills in a safe environment. There is evidence that SBL is superior to the traditional clinical teaching methods for acquisition of clinical skills. Although it is well established in resource rich settings, there is limited experience in resource limited settings and there is uncertainty regarding how SBL will be perceived among the stakeholders in medical education. As part of the steps leading to implementation of a SBL program at a university in Uganda, we sought to describe the perceptions of various stakeholders regarding the introduction of SBL methodology into learning at a medical school in Uganda.
Keywords: Medical simulation, Low and middle-income country, Simulation center, Stakeholders